Difficult-to-Treat or Resistant Hypertension: Etiology, Pathophysiology, and Innovative Therapies - Vasilios Papademetriou; Costas Tsioufis; Alan Gradman; Henry Punzi (International Journal of Hypertension)
Despite the many therapeutic options available today for the treatment of hypertension, a sizable number of patients still remain resistant to treatment. The prevalence of resistant hypertension in the general population under optimal conditions is about 3–5%. Although several factors and conditions can be identified and corrected a percentage of hypertensive patients remain with unacceptably high blood pressure levels. The high prevalence of hypertension in the general population renders this small percentage significant, in terms of actual patient numbers. This special issue of the journal expoars a whole spectrum of topics related to resistant hypertension: several articles address pathophysiolog and secondary causes of resistant hypertension and modern approaches to therapy. Of interest is the referance to the newer interventional approaches, that is, Baroreceptor stimulation therapy and catheter based sympathetic renal denervation.